Modèle de répartition du carbone assimilé dans une prairie naturelle - Randell, R. L., author; Paul, Eldor A., author; Warembourg, F. R., author; More, R. B., author; Gauthier-Villars, publisher (Colorado State University. Libraries, 1979)
A mathematical compartments model based on differential equations and describing the distribution of photoassimilated carbon in grassland is presented. The model includes four compartments: green leaf structure, dead leaves, roots structure and soil organic matter which represent the state variables. The input variable is the photosynthesis capacity of the leaves. The model output concerns primary production (aerial and below ground), root respiration as well as time variations of green biomass and root mass. The functional relations have been calculated from experimental results obtained after in situ labelling of native grassland with 14CO2 during the growing season (Matador prairie, Saskatchewan, Canada).The main objective of this modelling effort was to organize the results into a conceptual structure and to test the validity of the transfer coefficients obtained with the labelling techniques. The model output describes favorably the functioning of the system under study and therefore shows the advantages and potentialities of the use of 14C methods to describe the carbon dynamic in herbaceous communities.
Text in French; Summary in French and English.
Keywords: photoassimilated carbon; grasslands